2023
DOI: 10.1101/2023.02.25.529925
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A top-down slow breathing circuit that alleviates negative affect

Abstract: Breathing is profoundly influenced by both behavior and emotion and is the only physiological parameter that can be volitionally controlled. This indicates the presence of cortical-to-brainstem pathways that directly control brainstem breathing centers, but the neural circuit mechanisms of top-down breathing control remain poorly understood. Here, we identify neurons in the dorsal anterior cingulate cortex (dACC) that project to the pontine reticular nucleus caudalis (PnC) and function to slow breathing rates.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Both the TuS and NAc have outputs into downstream structures important for homeostatic regulation/control and limbic function. Ventral striatum spiny projection neurons also feedback upon the VTA in manners regulating DA release and this too could support, even if just bisynaptically, modulation of respiratory central pattern generators which are sensitive to dopamine (Sugita et al, 2015; Jhang et al, 2023). Perhaps one clue may reside from our results wherein we attempted to stimulate sniffing under anesthesia and found that DA release into the TuS or NAc is incapable of initiating sniffing ( Fig 5A & B ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the TuS and NAc have outputs into downstream structures important for homeostatic regulation/control and limbic function. Ventral striatum spiny projection neurons also feedback upon the VTA in manners regulating DA release and this too could support, even if just bisynaptically, modulation of respiratory central pattern generators which are sensitive to dopamine (Sugita et al, 2015; Jhang et al, 2023). Perhaps one clue may reside from our results wherein we attempted to stimulate sniffing under anesthesia and found that DA release into the TuS or NAc is incapable of initiating sniffing ( Fig 5A & B ).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the functional ‘sniffing’ output from the ventral striatum is within a structure which can drive changes in breathing but not under anesthesia. It is not uncommon for stimulation of some respiratory control centers to be incapable of altering respiration under anesthesia (Arthurs et al, 2023; Jhang et al, 2023). For instance, the ventral striatum projects to hypothalamic nuclei that are known to innervate respiratory control nuclei in the respiratory pons and could support entrainment of breathing at sniffing frequencies.…”
Section: Discussionmentioning
confidence: 99%